Anti-Inflammatory Effects of Plasma Circulating Exosomes Obtained from Normal-Weight and Obese Subjects on Hepatocytes - Afrisham, Reza; Sadegh-Nejadi, Sahar; Meshkani, Reza; Emamgholipour, Solaleh; Bagherieh, Molood; Paknejad, Maliheh (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Introduction: Obesity is a disorder with low-grade chronic inflammation that plays a key role in hepatic inflammation and steatosis. Moreover, there are studies to support the role of exosomes in cellular communications, the regulation of metabolic homeostasis and immunomodulatory activity. Accordingly, we aimed to evaluate the influence of plasma circulating exosomes derived from females with normal-weight and obesity on the secretion of inflammatory cytokines in human liver cells. Methods: Plasma circulating exosomes were isolated from four normal (N-Exo) and four obese (OExo) women. The exosomes were characterized and approved for CD63 expression (common exosomal protein marker) and morphology/size using the western blot and TEM methods, respectively. The exosomes were used for the stimulation of HepG2 cells in vitro. After 24 h of incubation, the protein levels of TNF-α, IL-6, and IL-1β were measured in the culture supernatant of HepG2 cells using the ELISA kit. Results: The protein levels of IL-6 and TNF-α in the cells treated with O-Exo and N-Exo reduced significantly in comparison with the control group (P=0.039 and P<0.001 respectively), while significant differences were not found between normal and obese groups (P=0.808, and P=0.978 respectively). However, no significant differences were found among the three groups in terms of IL-1β levels (P=0.069). Based on the correlation analysis, the protein levels of IL-6 were positively correlated with TNF-α (r 0.978, P<0.001). Conclusion: These findings suggest that plasma circulating exosomes have probably antiinflammatory properties independent of body mass index and may decrease the secretion of inflammatory cytokines in the liver. However, further in vitro and in vivo investigations are needed to address the anti-inflammatory function of N-Exo and O-Exo in human liver cells and/or other cells.
Keywords: interleukin-6